2016
DOI: 10.1002/acp.3204
|View full text |Cite
|
Sign up to set email alerts
|

The Productivity of Wh‐ Prompts when Children Testify

Abstract: Wh-prompts (what, how, why, who, when, and where) vary widely in their specificity and accuracy, but differences among them have largely been ignored in research examining the productivity of different question types in child testimony. We examined 120 six-to 12-year-olds' criminal court testimony in child sexual abuse cases to compare the productivity of various wh-prompts. We distinguished among wh-prompts, most notably the following: what/how-happen prompts focusing generally on events, what/how-dynamic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 32 publications
1
44
1
1
Order By: Relevance
“…On the one hand, this may suggest that children are not inclined to spontaneously mention information about clothing and that it is necessary for the interviewer to introduce the topic. Indeed, recent research has begun to investigate the most productive wh-questions in both forensic (Ahern, Andrews, Stolzenberg, & Lyon, 2015) and criminal settings Andrews, Ahern, Stolzenberg, & Lyon, 2016), with the recognition that some topics may require more specific inquiry.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, this may suggest that children are not inclined to spontaneously mention information about clothing and that it is necessary for the interviewer to introduce the topic. Indeed, recent research has begun to investigate the most productive wh-questions in both forensic (Ahern, Andrews, Stolzenberg, & Lyon, 2015) and criminal settings Andrews, Ahern, Stolzenberg, & Lyon, 2016), with the recognition that some topics may require more specific inquiry.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have examined lawyer‐child interactions using court transcripts from New Zealand [Hanna, Davies, Crothers, & Henderson, (18 cases); Zajac & Cannan, (15 cases); Zajac, Gross, & Hayne, (21 cases)] and the United States [Andrews, Ahern, Stolzenberg, & Lyon, in Press (120 cases); Andrews, Lamb, & Lyon, , (120 cases); Klemfluss, Quas, & Lyon, (42 cases); Stolzenberg & Lyon, (72 cases)]. In New Zealand and throughout the United Kingdom, children's direct testimony is provided to the court by way of pre‐recorded forensic interviews, sometimes supplemented by direct examination by prosecutors at the time of trial.…”
Section: Types Of Questions Asked By Lawyers In Courtmentioning
confidence: 99%
“…Children are also responsive in the courtroom. Both Andrews et al () and Klemfluss et al () found that child witnesses were more often responsive than unresponsive, although Andrews et al (, in Press) also reported that children were more responsive to prosecutors than defense lawyers and that productivity increased with age, with children more productive in response to open‐ended prompts than closed‐ended prompts. Similarly, Klemfluss et al () found that, with increasing age, children elaborated more (i.e., provided more information than was requested) in response to prosecutors' rather than defense lawyers' questions.…”
Section: Children's Responsiveness and Productivity In Courtmentioning
confidence: 99%
“…Research has consistently shown that, as one moves along the continuum, children provide fewer details and are more likely to include errors in their responses (Brown & Lamb, 2015). For very young children, however, the additional scaffolding provided by broadly framed 'wh-'questions appears to be particularly productive (Ahern, Andrews, Stolzenberg, & Lyon, 2015;Andrews, Ahern, Stolzenberg, & Lyon, 2016;Hershkowitz, Lamb, Orbach, Katz, & Horowitz, 2012;Stolzenberg & Lyon, 2017).…”
mentioning
confidence: 99%